Selection Framework for Evaluating Housing Technologies. (2015) - Nanyam, VPS Nihar; Basu, Riddha; Sawhney, Anil; Prasad, J.K.
Abstract: Recent survey by KPMG specifies that there is a requirement of 11 crore housing units to be built by 2022 in India. This leads to adoption of innovative technologies which have to be looked upon from the point of affordability as well as sustainability. As the Indian housing value chain is very complex, a plethora of factors and issues need to be addressed in this regard. Emerging technologies for building up the housing requirement are to be selected based on number of attributes. A scientific, holistic and transparent evaluation framework is not available to decide the appropriate technology. This paper highlights the evaluation framework consisting of mandatory attributes and preferred attributes, based on which the emerging housing technologies are selected for adoption. This framework is analyzed for two case studies to check the applicability.